2018
DOI: 10.1111/eci.12910
|View full text |Cite
|
Sign up to set email alerts
|

Relation of quality of anticoagulation control with different management systems among patients with atrial fibrillation: Data from FANTASIIA Registry

Abstract: About 60% of AF patients anticoagulated with VKAs had poor anticoagulation control (ie TTR<70%), and their management was only slightly better than when it is managed by general practitioners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
2
0
1
Order By: Relevance
“…One study in China (36) showed the percentage of people with TTR≥70 was only 10.7% while TTR ≤ 70% was 89.3% which indicated poor anticoagulation control of warfarin therapy in both countries. Interestingly, Nguyen et al (28) also reported lower TTR among their 512 Indigenous vs. nonindigenous Australian patients with AF [40 (29) vs. 50 (31); p = 0.006]. Based on the previous study by Golwala et al (37) black individuals had lower median TTRs (59%) than Hispanic (62%) and white (68%) participants; consistent with findings from the sub study of IMPACT trial (38).…”
Section: Time In Therapeutic Range Among Warfarin Users Within Different Ethnic Groupsmentioning
confidence: 55%
See 1 more Smart Citation
“…One study in China (36) showed the percentage of people with TTR≥70 was only 10.7% while TTR ≤ 70% was 89.3% which indicated poor anticoagulation control of warfarin therapy in both countries. Interestingly, Nguyen et al (28) also reported lower TTR among their 512 Indigenous vs. nonindigenous Australian patients with AF [40 (29) vs. 50 (31); p = 0.006]. Based on the previous study by Golwala et al (37) black individuals had lower median TTRs (59%) than Hispanic (62%) and white (68%) participants; consistent with findings from the sub study of IMPACT trial (38).…”
Section: Time In Therapeutic Range Among Warfarin Users Within Different Ethnic Groupsmentioning
confidence: 55%
“…Among the 18 studies ( 9 , 26 42 ) from the findings, eight studies ( 27 , 28 , 32 , 33 , 37 39 , 42 ) stated TTR among each specific ethnic groups in their population and the other 10 studies ( 9 , 29 31 , 34 37 , 40 , 41 ) only mentioned the TTR in their overall population (whites, Asians). So far, in Malaysia, there is no study being conducted that focused on TTR among different ethnic groups.…”
Section: Time In Therapeutic Range Among Warfarin Users Within Different Ethnic Groupsmentioning
confidence: 99%
“…, 27. - 28 . Esto tiene una gran importancia, ya que el mal control de la anticoagulación se asocia con un mayor riesgo de episodios adversos.…”
Section: ¿Qué Dicen Los Ensayos Clínicos?unclassified